การวิเคราะห์กระบวนการประเมินผลการเรียนรู้กลุ่มสาระการเรียนรู้วิทยาศาสตร์ : การวิจัยพหุกรณีศึกษาของครูต้นแบบและการวิจัยเชิงปริมาณ - พัชรีวรรณ สมเชื้อ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The aims of this research were 1) to specify the methods of a learning evaluation processes of master teachers in science strand, in Pratom Suksa level and Matayom Suksa level, within Bangkok Metropolis, 2) to survey the methods of a learning evaluation processes of teachers in science strand, in Pratom Suksa level and Matayom Suksa level, within Bangkok Metropolis 3) to analyze factors supporting and obstructing achievement of the methods in learning evaluation processes of teachers in science strand, in Pratom Suksa level and Matayom Suksa level, within Bangkok Metropolis, 3) to compare the methods of a learning evaluation processes of teachers who have different background, 4) to analyze the guideline promoting consistency of the learning evaluation processes with the national education reform. Two types of research methods were conducted. First, a qualitative study using a multi-case study research of three master teachers. The research instruments were interview and observation forms. Data were analyze by using content analysis. Second, a quantitative study was performed with the samples consisted of 349 master teachers in science strand from 158 schools in Bangkok Metropolis, using a simple random sampling. The research instruments was questionnaire with content validity by experts, and with construct validity using factor analysis. Data was analyzed through frequency, percentage, mean, standard deviation and multivariate analysis of variance : MANOVA. The major finding of the research were as follows: 1) Teachers produced learning plans, assessed learning outcomes and assessed congruously with student activities. The teacher found difficulties in diagnosing students’ strengths and weaknesses, in pre-test knowledge assessment, and in encouraging students to participation in assessment. The teachers used the methods of observation, authentic assessment and testing. The assessment outcomes were highly adopted to plan the learning activities. 2) Three master teachers complied with the national curriculum guideline 3) teacher who has different background will have different level of action. 4) The guideline promoting related to the learning evaluation processes with the national education reform were to be trained in the learning evaluation, to enhance implementation skills and to apply learning evaluation methods with appropriated school contexts.